2013
DOI: 10.3389/fpls.2013.00416
|View full text |Cite
|
Sign up to set email alerts
|

A phenomics approach to the analysis of the influence of glutathione on leaf area and abiotic stress tolerance in Arabidopsis thaliana

Abstract: Reduced glutathione (GSH) is an abundant low molecular weight plant thiol. It fulfills multiple functions in plant biology, many of which remain poorly characterized. A phenomics approach was therefore used to investigate the effects of glutathione homeostasis on growth and stress tolerance in Arabidopsis thaliana. Rosette leaf area was compared in mutants that are either defective in GSH synthesis (cad2, pad2, and rax1) or the export of γ-glutamylcysteine and GSH from the chloroplast (clt) and in wild-type pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…The fresh weight of the aerial parts of the mutants grown under control- and P-lim conditions was approximately 70% of that of the WT plants. These findings suggest that, under the no-stress condition, the GSH1 mutations were silent at the aerial parts, although the mutants were shown to have impaired lateral root density ( Schnaubelt et al, 2013 , 2015 ). Therefore, since the applied stress treatments did not result in severe growth inhibition in the assayed plants, we considered them as mild stress treatments ( Figures 1A,B and Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The fresh weight of the aerial parts of the mutants grown under control- and P-lim conditions was approximately 70% of that of the WT plants. These findings suggest that, under the no-stress condition, the GSH1 mutations were silent at the aerial parts, although the mutants were shown to have impaired lateral root density ( Schnaubelt et al, 2013 , 2015 ). Therefore, since the applied stress treatments did not result in severe growth inhibition in the assayed plants, we considered them as mild stress treatments ( Figures 1A,B and Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 92%
“…Low glutathione levels do not largely affect the shoot phenotypes of glutathione synthesis mutants under no-stress conditions. The characterization of leaf area phenotypes by using a high-resolution phenomic approach showed that glutathione synthesis mutants, except for an allele of GSH1 mutant called regulator of APX2 1-1 ( rax1-1 ) ( Ball et al, 2004 ), were not as sensitive as the WT plants under 1 μM MV treatment ( Schnaubelt et al, 2013 ). We found that the two GSH1 mutants ( cad2-1 and pad2-1 ), GSH1 -overexpressing plants [7-5 and 13-6 ( Cheng et al, 2015 )], and WT plants exhibited a similar level of growth reduction under the mild MV stress condition ( Figure 1 and Supplementary Figure S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24] Apart from heavy metals, the role of GSH has also been well documented in providing resistance against other abiotic stresses. 25,26 These processes require efficient sulfur uptake and homeostasis in plants which is dependent on multigene family encoding sulfate transporters. 27 Comparative transcriptome analyses of arsenate [As(V)] and arsenite [As(III)] stress in rice seedlings demonstrated differential expression of sulfate-metabolizing proteins and transporters including sulfate transporter.…”
mentioning
confidence: 99%
“…Glutamate cysteine ligase (GCL) is a key enzyme involved in glutathione biosynthesis and is encoded by the GSH1 gene [63]. GCL is an essential component of the plant defence system in the detoxification of reactive oxygen species [64,65]. For instance, Arabidopsis plants with an identified mutation in the gene encoding the GCL enzyme showed higher susceptibility to biotic stress [66].…”
Section: Discussionmentioning
confidence: 99%